Kebijakan Pengembangan Koleksi di Perpustakaan SMA Negeri 1 Kajen - Jayidatul Musyafiqoh (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This study examines the collection development policies and strategies at SMA Negeri 1 Kajen library. This study uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that the collection development process involves analyzing user needs, selecting library materials relevant to the curriculum, and collaborating with related parties. Despite limited budgets and resources, routine collection evaluations are conducted to ensure collection quality. The study concludes that collection development is effective, but there is a need for systematic written policies and long-term plans. Recommendations are directed toward strengthening policies and strategies for the sustainability of the library as a learning resource.